STRATEGI POLITIK LUAR NEGERI IRAN MENGATASI SANKSI EMBARGO PADA TAHUN 2012-2014 - Dewi Palupi Sukmawardani (HI 16 UMY 074, 2016)
*74 STRATEGIPOLITIKLUARNEGERIIRANMENGATASISANKSI EMBARGOPADATAHUN2012-2014